Comparison of procedures for nitrate determination in vegetable tissue - Mantovani, José Ricardo; Cruz, Mara Cristina Pessôa da; Ferreira, Manoel Evaristo; Barbosa, José Carlos (Pesquisa Agropecuaria Brasileira, 2005)
Nitrate content determination is important for food quality evaluation, but its determination is affected by interferences. The objective of this work was to compare nitrate determination procedures for vegetable tissues. In dry matter samples from three lettuce cultivars that received five levels of nitrogen in a greenhouse experiment, nitrate was extracted with deionized water and its determination was made by the cadmium column method, the distillation method, the salicylic acid method, and the method using the reductive mixture with zinc. The salicylic acid method and that of reductive mixture with zinc overestimated the nitrate content in lettuce dry matter, because they were influenced by the color of dry matter extracts and other interferences. The cadmium column and the distillation methods are the best for nitrate determination in vegetable tissues, but the simplicity and lower cost of distillation in relation to cadmium column method suggest that the first one must be recommended.
Keywords: Lactuca sativa; plant analysis; nitrogen